2019
DOI: 10.1002/rth2.12184
|View full text |Cite
|
Sign up to set email alerts
|

The mode of anesthesia influences outcome in mouse models of arterial thrombosis

Abstract: Background Arterial thrombosis models are important for preclinical evaluation of antithrombotics but how anesthetic protocol can influence experimental results is not studied. Objectives We studied how three most commonly used rodent anesthetics affect the induction of thrombosis and thrombus resolution with antiplatelet agent integrilin (Eptifibatide). Methods The Folts, electrolytic, and FeCl 3 models of carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…This inhibitory effect could artefactually alter the size and structure of thrombi seen in current animal thrombosis models, potentially leading to an overestimation of the effectiveness of putative anti-platelet therapies. This is consistent with previous findings that show that the use of different anaesthetics differentially impacts the efficacy of integrin αIIbβ3 blockers in murine thrombosis models [ 39 ], thus providing initial evidence that our model system is a potential alternative to current in vivo studies. A more detailed side-by-side comparison examining the impact of different anaesthetics on the thrombotic response in current in vivo models, and in the TEBV model presented here, will be required to fully validate the model system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This inhibitory effect could artefactually alter the size and structure of thrombi seen in current animal thrombosis models, potentially leading to an overestimation of the effectiveness of putative anti-platelet therapies. This is consistent with previous findings that show that the use of different anaesthetics differentially impacts the efficacy of integrin αIIbβ3 blockers in murine thrombosis models [ 39 ], thus providing initial evidence that our model system is a potential alternative to current in vivo studies. A more detailed side-by-side comparison examining the impact of different anaesthetics on the thrombotic response in current in vivo models, and in the TEBV model presented here, will be required to fully validate the model system.…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments, we observed that ketamine almost completely inhibits thrombus formation upon the TEML construct. It is possible that this effect is caused by the inhibition of dense granule secretion by ketamine, as autocrine signalling molecules released from here are known to be crucial to the recruitment of circulating platelets onto the surface of forming thrombi [ 7 , 39 ]. This inhibitory effect could artefactually alter the size and structure of thrombi seen in current animal thrombosis models, potentially leading to an overestimation of the effectiveness of putative anti-platelet therapies.…”
Section: Discussionmentioning
confidence: 99%
“…All data for mice were obtained in experiments performed under general anesthesia, using isoflurane, ketamine–xylazine, and pentobarbital sodium, which are known to affect the cardiorespiratory system including but not limited to peripheral perfusion, vessel diameter, and heart rate 14 . Although the effects are moderate, and do not affect general validity of the comparisons between vessels and applicability of the data to ex vivo models (the same anesthesia and young mice are typically used for in vivo thrombosis experiments, unless specific efforts are undertaken to counter this at least partially), these conditions should be noted as an important source of systemic changes for in vivo thrombosis studies 15 . Furthermore, the data provided are average values for healthy (when possible) vessels of humans and of young mice.…”
Section: Inventory Of Flow Conditionsmentioning
confidence: 99%
“…Unlike the paper by Qiao et al, we did not see altered enzyme levels in mice receiving chemotherapy alone ( 19 ). Carstairs staining is routinely for histological detection of platelets/fibrin/collagen/red cells in thrombi ( 28 ). Automated image quantitation of the fibrin-rich areas revealed a significant increase in fibrin deposits in the BM+T cells cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological changes in the liver, intestine and skin were quantified in randomly selected 20x micrographs from 3 different 5 µm sections (10 images per mouse) by a 0-3-point score by a trained pathologist blinded to experimental groups. Liver sections stained with Carstairs stain by the Monash Histology Platform; Carstairs staining was quantified as published ( 28 ).…”
Section: Methodsmentioning
confidence: 99%